If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5+4t=7(t)
We simplify the equation to the form, which is simple to understand
5+4t=7(t)
Reorder the terms in parentheses
5+4t=+(+7t)
Remove unnecessary parentheses
+5+4t=+7t
We move all terms containing t to the left and all other terms to the right.
+4t-7t=-5
We simplify left and right side of the equation.
-3t=-5
We divide both sides of the equation by -3 to get t.
t=1.66666666667
| -16x^2+60x=56 | | 4a+3(a-2)=2(3a-2) | | 2(4x+3)+4=3x(2x+4) | | 3(x-2)=9(9x+2) | | (-8+5i)(-7+3i)= | | 15-3(2x-9)+x=115 | | -16x^2+6x=56 | | 69.1=3.14*r | | 0.06(y-9)+0.20y=0.16y-0.01(60) | | -6.1x+108.8= | | 6(5n+7)-4(4n+6)=-24 | | 5+4n=7+n | | 4y+2+y=180 | | 19x-9x=20 | | 9x+8=x+40 | | -7.5x+102.3= | | 5+4n=7n | | -6(b-7)-2(b+6)=30 | | 6w+2-3w=26 | | -(3x-5)+2x=7 | | -4f+1= | | 4y+60=9y | | 1000x+50=30 | | -1+m=m-8 | | -27y=-108 | | -6x^2+3=-15 | | 4y+2=180 | | -6f+1=13 | | 3x+60=10x+11 | | 23=-7(6v+7)+5(1-5v) | | 1.9/250=x/650 | | y-18=21 |